2014
DOI: 10.5489/cuaj.1769
|View full text |Cite
|
Sign up to set email alerts
|

Late renal vein aneurysm following living related renal transplant

Abstract: Renal vein aneurysms are rare; there are less than 10 reported cases. As of yet there have been no reported cases of renal vein aneurysm following renal transplantation. We present a case of an incidentally discovered renal vein aneurysm following uncomplicated living related renal transplant. The lesion was discovered 4 years after the transplant through abdominal ultrasound investigation of new right lower quadrant discomfort. Magnetic resonance imaging confirmed the presence of a 2.3-cm thrombosed renal vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…[7][8][9] Dale and colleagues reported late RVA formation 4 years after renal transplantation. 10 Most of the experience of surgical interventions for RVAs reported in the literature are related to nutcracker syndrome. 16 Although several surgical techniques have been reported, most commonly used are direct reimplantation of the LRV to IVC, LRV bypass, and renal autotransplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Dale and colleagues reported late RVA formation 4 years after renal transplantation. 10 Most of the experience of surgical interventions for RVAs reported in the literature are related to nutcracker syndrome. 16 Although several surgical techniques have been reported, most commonly used are direct reimplantation of the LRV to IVC, LRV bypass, and renal autotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent PubMed query (April 2016; with the key words ''renal,'' ''vein,'' and ''aneurysm'') identified only 14 cases in the English literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The RVAs may be broadly classified as primary or secondary. Primary RVAs are probably related to congenital weakness of the venous wall with an associated underdevelopment of the media.…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed of 12 other RVAs in adults reported in the English-language literature (Table 1). [1][2][3][4][5][6][7][8][9] It was previously reported that the left renal vein was the most common involved vessel. 1 However, no such preference was demonstrated in these 13 reviewed RVAs.…”
mentioning
confidence: 99%